A Note on Inclusion Properties of Weighted Orlicz Spaces - Masta, Al Azhary; -, Ifronika; Taqiyuddin, Muhammad (Journal of the Indonesian Mathematical Society, 2020)
In this paper we present sufficient and necessary conditions for the inclusion relation between two weighted Orlicz spaces which complete the Osançliol result in 2014. One of the keys to prove our results is to use the norm of the characteristic functions of the balls in $\mathbb{R}^n$.